Biomechanical Comparison of Polymeric Spinal Cages Using Ct Based Finite Element Method - Muhammad Hilmi, Jalil; Muhammad Hazli, Mazlan; Todo, Mitsugu (International Academy Publishing (IAP), 2017)
Interbody fusion devices are gaining acceptance as a treatment method of mainly for disc degeneration diseases and other medical conditions. Posterior lumbar interbody fusion (PLIF) cage is used in the procedure to maintain stability and promote fusion between vertebrae. Poly lactic acid (PLA) is assumed to be the alternative material which could provide cheaper material and lower production cost. However, these implants often cause subsidence failure at the endplate, resulting in injury risk and mechanical instability during fusion. In this study, the stress behavior of PLIF cage made by two different materials, Polyether ether ketone (PEEK) and PLA; was studied using finite element method (FEM). By implementing bilateral cages between vertebral bone L4 and L5, and conducting 6 different motion activities onto the model, the stress distribution of L4-L5, and cage bodies was predicted. Simulation results predicted that the cage subsidence occurred at both materials, with an overall of higher cage-endplate stresses for PEEK, in comparison to PLA and controlled configurations. In addition, the stress distribution in PLA cage was better and the maximum von Mises stress was approximately 3 times lower than PEEK cage. Further investigation of PLA cage’s mechanical properties should be done experimentally to determine the accuracy and reliability of the simulation.